Preparation of ZnO nanoparticles using a rotating packed bed. Issue 15 (15th November 2016) - Lin, Chia-Chang; Lin, Yung-Chieh
Abstract: Zinc oxide (ZnO) nanoparticles can be prepared by the precipitation method in a rotating packed bed (RPB). In this work, precursors were firstly prepared in a continuous mode using the liquid-liquid reaction of zinc chloride (ZnCl2 ) and sodium hydroxide (NaOH). The effects of the molar ratio of ZnCl2 to NaOH, the flow rates of aqueous ZnCl2 and NaOH, the rotational speed, and the concentrations of ZnCl2 and NaOH on the size of the precursors were examined. Experimental results demonstrate that larger flow rates of the reactant and precipitant, a higher rotational speed, and higher concentrations of ZnCl2 and NaOH were associated with smaller precursors. The smallest precursors were obtained at a ZnCl2 concentration of 0.8 mol/L, an NaOH concentration of 1.6 mol/L, a rotational speed of 2000 rpm, and flow rates of 0.5 L/min. Then, the aforementioned precursors were calcined at 450 °C for 1 h to yield ZnO nanoparticles with a mean size of 68 nm and a rather narrow size distribution. The photocatalytic activity of ZnO nanoparticles was evaluated by the photocatalytic decolorization of methyl orange. After 3 L of aqueous methyl orange had been photodegraded by ZnO nanoparticles for 200 min, the decolorization efficiency of methyl orange was found to be 84%.